PERAN RELAWAN DEMOKRASI DALAM MENINGKATKAN PARTISIPASI PEMILIH MILENIAL PADA PEMILU 2019 DI KABUPATEN SUMENEP - Moh Ikmal (PRODI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN STKIP PGRI SUMENEP, 2021)
This study aims to determine the role of internet-based democracy volunteers to increase the participation of millennial society in the 2019. This research uses a qualitative approach that reveals findings and describes comprehensively about the data obtained in the field. The method used by researchers is online interviews and using valid data from trusted sources. The results of this study indicate that internet-based democratic volunteers are quite effective in efforts to increase election participation in 2019. This can be seen from KPU data collection where there is an increase in participation in 2019 when compared to 2014, this is because democratic volunteers are considered successful because they are able to increase 2019 election participation in Sumenep district. Researchers also revealed the systematic and work agenda of democratic volunteers. Internet-based democracy volunteers play a large role in efforts to increase public participation in elections, internet-based democracy volunteers as working partners of the KPU are tasked with disseminating information on various social media about the importance of elections, providing education on voting procedures, distinguishing types of ballots, anti-hoax and anti-campaign campaigns. abstentions. The researcher also found that the election results were accumulated and were not classified based on the age of the voters, although the data before the election separated and categorized the data, but after the election the election organizer only counted the number of voters in general.